Exploring servitization through the paradox lens : Coping practices in servitization - Kohtamäki, Marko; Einola, Suvi; Rabetino, Rodrigo (Elsevier, 2020)
The study analyzes the coping practices that emerge when a manufacturer of standardized products and add-on services expands to provide customized solutions. Based on a comparative case study methodology conducted across four case companies, and an analysis of extensive documentary data, the study challenges the dichotomous ‘either-or thinking’ in servitization research and highlights ‘both-and thinking’ by identifying both paradoxes and coping practices. The study extends the literature by identifying four paradoxes in servitization: 1) effectiveness in the customization of solutions vs. efficiency in product manufacturing, 2) building a customer orientation vs. maintaining an engineering mindset, 3) organizing product and service integration vs. separated services and product organizations, and 4) exploratory innovation in solutions vs. exploitative innovation in product manufacturing. Moreover, the study identifies nine practices that manufacturing companies apply when coping with the paradoxical challenges that emerge during servitization. The findings may help manufacturing companies understand, accept, and address paradoxical challenges and balance tensions, as not all tensions can be resolved. The identification of these paradoxes allows us to understand the difficulties that manufacturing companies face during the servitization process and may help explain the servitization-deservitization trend among some manufacturing companies that some recent studies have identified.
Keywords: Servitization and digital servitization; Paradox theory; Product-service systems (PSS); Strategic change; Coping practices; Strategy-as-practice (SAP, Practice theory); fi=Johtaminen ja organisaatiot|en=Management and Organization|